Discussing with Juan Auz. Challenges of Climate Litigation with a Human Rights Approach - Montalván-Zambrano, Digno (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
This paper presents some of the challenges of the proposal in favor of implementing a human rights approach to climate litigation, advocated by Professor Juan Auz in the previous number of this review. I argue that, while this idea may help victims participate in climate change decision-making, the relationship between climate law and human rights is not entirely peaceful. Specifically, I point out that the individual, remedial and territorial focus of human rights limits their ability to address global-scale environmental problems such as climate change. On the other side, I point out the risks of the determination of harm to human rights based on an exclusively global view of environmental problems. In line with the above, I present the elements that make complex the attribution of state responsibilities for human rights violations caused by climate change. Finally, I point out the tensions that exist between dependence of climate litigation on Western science and other forms of knowledge, such as those of indigenous peoples.
Keywords: Climate litigation; human rights; environmental litigation; climate science; environmental damage